Caminhantes aleatórios sonolentos: análise exata em sistemas pequenos e simulações de Monte Carlo - Julio Cesar Mansur Filho (2012)
In this work we study symmetric sleepy random walkers, a model exhibiting an absorbingstate phase transition in the conserved directed percolation (CDP) universality class. Unlike most examples of this class studied previously, this model possesses a continuously variable control parameter, facilitating analysis of critical properties. We study the modelusing two complementary approaches: analysis of the numerically exact quasistationary (QS) probability distribution on rings of up to 22 sites, and Monte Carlo simulation of systems of up to 32000 sites. The resulting estimates for critical exponents , /, and z, and the moment ratio m211 = <p2>/ 2 (p is the activity density), based on finitesize scaling at the critical point, are in agreement with previous results for the CDPuniversality class. We find, however, that the approach to the QS regime is characterized by a different value of the dynamic exponent z than found in the QS regime.